2017
DOI: 10.1038/s41598-017-18170-8
|View full text |Cite
|
Sign up to set email alerts
|

Coverage-dependent essential properties of halogenated graphene: A DFT study

Abstract: The significant halogenation effects on the essential properties of graphene are investigated by the first-principles method. The geometric structures, electronic properties, and magnetic configurations are greatly diversified under the various halogen adsorptions. Fluorination, with the strong multi-orbital chemical bondings, can create the buckled graphene structure, while the other halogenations do not change the planar s bonding in the presence of single-orbital hybridization. Electronic structures consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 74 publications
(99 reference statements)
2
11
0
Order By: Relevance
“…This assumption was called into question by the discovery that the fully fluorinated graphene derivative fluorographene (FG) undergoes chemical transformations involving substitution and reductive defluorination under rather mild reaction conditions. It was later shown that this material’s surprising reactivity may originate from the presence of point radical defects. , In addition, high-resolution F 1s X-ray photoelectron spectra of FG and partially fluorinated graphenes (pFGs) feature several peaks that can be attributed to different kinds of C–F bonds. , Theoretical studies on graphene fluorination suggested that the covalent bonding of a single fluorine ad-atom to a graphene sheet is relatively weak, with estimated bond dissociation energies (BDEs) of 44.9 kcal/mol for infinite dilute limit and 46.9 kcal/mol corresponding to a low-density FG with a degree of fluorination of ∼3 at. %, whereas the BDE of the prototypical C–F bond is 105.4 kcal/mol . On the other hand, the bonding of a single fluorine ad-atom to graphene is stronger than that of other ad-atoms that can adsorb to the top position on a graphene sheet (C–H bond 43.7 kcal/mol, C–Cl bond 29.9 kcal/mol, C–Br bond 23.0 kcal/mol, and C–I bond 18.4 kcal/mol) …”
Section: Introductionmentioning
confidence: 99%
“…This assumption was called into question by the discovery that the fully fluorinated graphene derivative fluorographene (FG) undergoes chemical transformations involving substitution and reductive defluorination under rather mild reaction conditions. It was later shown that this material’s surprising reactivity may originate from the presence of point radical defects. , In addition, high-resolution F 1s X-ray photoelectron spectra of FG and partially fluorinated graphenes (pFGs) feature several peaks that can be attributed to different kinds of C–F bonds. , Theoretical studies on graphene fluorination suggested that the covalent bonding of a single fluorine ad-atom to a graphene sheet is relatively weak, with estimated bond dissociation energies (BDEs) of 44.9 kcal/mol for infinite dilute limit and 46.9 kcal/mol corresponding to a low-density FG with a degree of fluorination of ∼3 at. %, whereas the BDE of the prototypical C–F bond is 105.4 kcal/mol . On the other hand, the bonding of a single fluorine ad-atom to graphene is stronger than that of other ad-atoms that can adsorb to the top position on a graphene sheet (C–H bond 43.7 kcal/mol, C–Cl bond 29.9 kcal/mol, C–Br bond 23.0 kcal/mol, and C–I bond 18.4 kcal/mol) …”
Section: Introductionmentioning
confidence: 99%
“…Among the halogen adatoms, the magnitude of binding energy declines with the increase of the atomic number [Tables 1 and 2], i.e., the F-adsorbed systems achieve the lowest binding energy eV–−4.7 eV. Furthermore, the halogen-absorbed silicene [Tables 1 and 2] possesses a higher geometric stability than halogen-adsorbed graphene 49 because of its highly reactive buckled surface. The shortest halogen-Si bond length is revealed in the F-adsorbed system Å–1.64 Å, due to its smallest atomic number among halogen atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Both experimental and theoretical efforts have revealed that chemical functionalizations of the carbon allotropes with adatom (H, F, O, and so forth) and ad-molecules (OH) can modify the hybridization of carbons. Hydrogenation , and halogenation (especially with fluorine atoms) ,, of graphene have been intensively investigated in recent years because of their many unique properties. For instance, hydrogenation in graphene transforms the hybridization of carbon from sp 2 to sp 3 , changes its nature of electronic states from the semimetallic feature into a wide band gap semiconductor and induces magnetic moments and the extreme modification of the optoelectronic and transport properties. , Very recently, Kilic et.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Recently, much progress has been made on the preparation and control of CF bonding characters, F/C ratios (the F/C ratio is defined as the mole ratio of fluorine to carbon), and configurations of fluorinated graphene. 19,25 In this present work, we have studied the chemical functionalization of TH-carbon by introducing fluorine atoms with various configurations such as single-and double-sided fluorination. Using first-principles density-functional theory (DFT) calculations, we have studied the stability of TH-carbon and its fluorinated derivatives from the energetic, dynamic, thermal, and mechanical aspects with the results of binding energy, phonon band structure, thermal stability, and elastic constants, respectively.…”
Section: ■ Introductionmentioning
confidence: 99%